2001
DOI: 10.1165/ajrcmb.24.1.4024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Human Glucocorticoid Receptor α and β Isoforms in Human Respiratory Epithelial Cells and Their Regulation by Dexamethasone

Abstract: Two isoforms of the human glucocorticoid receptor (hGR) have been described, hGRalpha and hGRbeta. We analyzed the expression and regulation of both hGR isoforms in human respiratory epithelial cells (BEAS-2B, A549, and primary nasal epithelial cells). In BEAS-2B cells, the expression of hGRalpha messenger RNA (mRNA) was much higher than that of hGRbeta mRNA. Dexamethasone (DEX) (10(-6) M) downregulated hGRalpha mRNA at 6 and 24 h (55 +/- 8 and 58 +/- 5% of control, respectively; P < 0.01), whereas it decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 33 publications
6
78
1
3
Order By: Relevance
“…To this end, we observed that in experiments carried out to 24 h, exposure of 29-day GA preterm rabbits to Dex after 12 h actually caused a decrease in basal lung GCR protein levels that was apparent up to 24 h. The data presented herein suggesting receptor downregulation by its cognate ligand in whole lung are in similar agreement with another published study that reported a downregulation of GCR protein levels by Dex in cultured human airway epithelial cells (40). Further analysis of our data demonstrates that postnatal treatment of 29-day GA preterm rabbits with Dex over a period of 16 h resulted in an elevation of lung GCR mRNA expression that was concurrent with the decline in protein levels, suggestive of a transcriptional mode of upregulating gene expression in response to the posttranslational mechanism of downregulating existing protein levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To this end, we observed that in experiments carried out to 24 h, exposure of 29-day GA preterm rabbits to Dex after 12 h actually caused a decrease in basal lung GCR protein levels that was apparent up to 24 h. The data presented herein suggesting receptor downregulation by its cognate ligand in whole lung are in similar agreement with another published study that reported a downregulation of GCR protein levels by Dex in cultured human airway epithelial cells (40). Further analysis of our data demonstrates that postnatal treatment of 29-day GA preterm rabbits with Dex over a period of 16 h resulted in an elevation of lung GCR mRNA expression that was concurrent with the decline in protein levels, suggestive of a transcriptional mode of upregulating gene expression in response to the posttranslational mechanism of downregulating existing protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…7A). Western blot analysis of the ␣-subunit of GCR detected, as previously reported, the 94-kDa protein in rabbit lung samples (8,40). GCR lung protein levels were evident in 23-and 27-day GA preterm rabbits and were elevated 1.8-fold (by densitometric analysis) from 27 to 29 days' GA (Fig.…”
Section: Dex-induced ␣-Enac Upregulation Occurs Via Binding To Gcr Insupporting
confidence: 79%
See 1 more Smart Citation
“…GR-␣ receptors are functional, whereas GR-␤ receptors are not; therefore, an increase in the number of GR-␤ receptors could lead to decreased binding and activity of glucocorticoids in vivo. 106,107 Altered corticosteroid cell-signaling systems may also play a role.…”
Section: Mechanisms Of Corticosteroid Resistancementioning
confidence: 99%
“…TBP, TATA-binding protein. c d translation are linked, in a way that when translation is inhibited the mRNA is stabilized (17). GR-induced transcriptional responses are proportional to the number of receptor molecules present in the cell (18).…”
Section: Nuclear Available Gr and Gc Responsementioning
confidence: 99%